Structure of Production based on Backward and Forward Linkages: the Case of China and USA - Rumiana GÓRSKA (Communications of International Proceedings, 2021)
Economic competition between countries takes place in many fields. One of them is changing structure of production. The main purpose of the article is to investigate and compare the evolution of the structure of production of two big economies – these of the USA and China – using input-output framework during the last 45 years period. The data used in the study come from the symmetrical input-output tables for the period of 1970-2015 year. The comparative analysis revealed that the structure of production of these big economies as well as its time evolution differs. The differences concern the identified key industries, the strength of linkages between industries and in effect the economic “landscape” of the countries.
Keywords: input-output analysis; backward linkages; forward linkages